RELATION BETWEEN AGING MALE SYMPTOM SCORE (AMS SCORE) AND AGE - Ghinorawa, Tanaya; Rahardjo, Djoko (Indonesian Journal of Urology, 2010)
Objective: To study the relation of the Aging Male Symptom Score (AMS score) with age groups, and to find the age when the AMS score increases. Material & method: In all, 347 patients with age beginning at 50 years underwent an interview with the AMS Score questionnaire, then they were divided according to age in groups, less than or equal to 50 years, 51 – 55 years, 56 – 60 years, and more than 60 years. Results: In the age group less than or equal to 50 years, there were 26 men (7,5%). With an abnormal AMS psychology, there were 18 men, with abnormal AMS somatovegetative score there were 20 men, with an abnormal AMS sexual score 20 men, and with abnormal total AMS Score 14 men. In the age group 51 – 55 years, there were 146 men (42,07%), with an abnormal AMS psychology in 75 men, with abnormal AMS somatovegetative score 114 men, abnormal AMS sexual in 123 men, and abnormal total AMS Score in 71 men. In age group 56 - 60 years there were 48 men (13,83%), abnormal AMS psychology in 35 men, abnormal AMS somatovegetative score in 44 men, abnormal AMS sexual in 45 men, and abnormal total AMS Score in 35 men. In the age group of more than 60 years, there were 127 men (36,6%), abnormal AMS psychology was found in 87 men, abnormal AMS somatovegetative score in 112 men, abnormal AMS total sexual score 122 men, and abnormal total AMS score was in 96 men. All of the AMS score values significantly increased after 55 years old, p value at AMS psychology was 0,005, AMS somatovegetative was 0,000, AMS sexual was 0,000, and at total AMS Score was 0,000. To define the age when AMS score increases. The conclusion was that AMS psychology values begin to increase after 55 years (sensitivity 69,71, specificity 45,93), AMS somatovegetative values increase after 55 years (sensitivity 89,14, specificity 22,09), and total AMS score value begins to increase at 55 years (sensitivity 74,86, specificity 50,58). However, AMS sexual value increase at 50 years (sensitivity 90,34, specificity 23,08). Conclusion: All of the AMS score values increase significantly at 55 years.